(untitled) (Global Journal of Computer Science and Technology, 2012)
In this paper we have studied the concept and need of Multiclass classification in scientific research. Various classification approaches are discussed in brief. Support Vector Machines (SVM) has well known record in Binary Classification. Our major emphasis in this paper is to study the fitness of Support Vector Machines in multiclass classification.